Anticoccidial activity of fruit peel of Punica granatum L. (March 2018) - Ahad, Shazia; Tanveer, Syed; Malik, Tauseef Ahmad; Nawchoo, Irshad Ahmad
Abstract: In the interests of food safety and public health, plants and their compounds are now re-emerging as an alternative approach to treat parasitic diseases. Here, we studied the anticoccidial effect of different solvent extracts of the fruit peel of Punica granatum -a commercial waste from pomegranate juice industries. The hope underlying these experiments was to find a sustainable natural product for controlling coccidiosis. The plant extracts were prepared using solvents of different polarity. Acute oral toxicity study was first carried out to see the safety of crude extracts. A high dose of crude extracts (300 mg/kg body weight) was tested for possession of anticoccidial activity against experimentally induced coccidial infection in broiler chicken. Activity was measured in comparison to the reference drug amprolium on the basis of oocyst output reduction, mean weight gain of birds and feed conversion ratio. Oocyst output was measured using Mc-Masters counting technique. Acute oral toxicity study showed that crude extracts of P. granatum are safe up to dosage of 2000 mg/kg body weight. LD 50 was not determined as mortalities were not recorded in any of the five groups of chicken. For anticoccidial activity crude methanolic extract (CME) of the fruit peel of P. granatum showed the maximum effect as evident by oocyst output reduction (92.8 ± 15.3), weight gain of birds (1403.0 ± 11.9 g) and feed conversion ratio (1.66 ± 0.04), thereby affirming the presence of alcohol soluble active ingredients in the plant. We also tested different doses (100–400 mg/kg body weight) of the CME of the fruit peel of P. granatum, the most active extract on E. tenella and observed a dose dependent effect. From the present study it can be concluded that alcoholic extract of the fruit peel of P. granatum has significant potential to contribute to the control of coccidian parasites of chicken. Graphical abstract: Image 1 Highlights: Fruit peel of Punica granatum was tested for controlling Eimeria tenella . Toxicity study showed that the crude extracts of fruit peel of P. granatum are safe up to dosage of 2000 mg/kg body weight. Crude methanolic extract of fruit peel of P. granatum was found to be most effective .